The Effects of Basal Insulin Suspension at the Start of Exercise on Blood Glucose Levels During Continuous Versus Circuit-Based Exercise in Individuals with Type 1 Diabetes on Continuous Subcutaneous Insulin Infusion - Zaharieva, Dessi (Diabetes Technol Ther, 2017)
Background: Exercise causes glycemic disturbances in individuals with type 1 diabetes (T1D). Continuous moderate-intensity aerobic exercise (CON) generally lowers blood glucose (BG) levels and often leads to hypoglycemia. In comparison, circuit-based exercise (CIRC) may attenuate the drop in BG. The goal of this study is to contrast the effects of basal insulin suspension at the onset of two different forms of exercise (CON vs. CIRC). Methods: Twelve individuals (six men and six women) with T1D on insulin pump therapy were recruited for the study. All participants completed a maximal aerobic fitness test and two 40-min exercise sessions, consisting of either continuous treadmill walking or a circuit workout. Basal insulin infusion was stopped at the onset of exercise and resumed in recovery. After providing an initial reference value, volunteers were blinded to their [BG] and were asked to estimate their levels during exercise. Results: Oxygen consumption (47.5 ± 7.5 vs. 54.5 ± 13.5 mL·kg(−1)·min(−1), P = 0.03) and heart rate (122 ± 20 vs. 144 ± 20 bpm, P = 0.003) were lower in CON vs. CIRC. Despite the lower workload, BG levels dropped more with CON vs. CIRC (delta BG = −3.8 ± 1.5 vs. −0.5 ± 3.0 mmol/L for CON vs. CIRC, respectively, P = 0.001). Participants were able to estimate their BG more accurately during CON (r = 0.83) vs. CIRC (r = 0.33) based on a regression analysis. Conclusion: Despite a lower intensity of exercise, with full basal insulin suspension at the start of exercise, CON results in a larger drop in BG vs. CIRC. These findings have implications for single hormone-based artificial pancreas development for exercise. While this study does not negate the importance of frequent capillary BG monitoring during exercise, it does suggest that if persons are knowledgeable about their pre-exercise BG levels, they can accurately perceive the changes in BG during CON, but not during CIRC.